Understanding COVID-19-associated endothelial dysfunction: role of PIEZO1 as a potential therapeutic target - Zhang, Xiaoting; Liu, Jinhai; Deng, Xiaoming; Bo, Lulong (Frontiers in Immunology, 2024)
) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Due to its high infectivity, the pandemic has rapidly spread and become a global health crisis. Emerging evidence indicates that endothelial dysfunction may play a central role in the multiorgan injuries associated with COVID-19. Therefore, there is an urgent need to discover and validate novel therapeutic strategies targeting endothelial cells. PIEZO1, a mechanosensitive (MS) ion channel highly expressed in the blood vessels of various tissues, has garnered increasing attention for its potential involvement in the regulation of inflammation, thrombosis, and endothelial integrity. This review aims to provide a novel perspective on the potential role of PIEZO1 as a promising target for mitigating COVID-19-associated endothelial dysfunction.